Senior High School Mathematics E-Module Based on STEM Orienting to Higher Order Thinking Skills Questions - I Komang Sukendra; I Wayan Widana; I Dewa Putu Juwana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
At present schools have find difficulty providing teaching materials to support textbooks. Therefore, it is necessary to develop teaching materials in the form of e-modules. The research aimed to develop senior high school mathematics e-module high-quality based on STEM orienting to HOTS questions.. The research used the development of Plomp model. The phase of the model involved; the beginning investigation phase, design phase, realization/construction phase, test phase, evaluation, revision, and implementation phases. The validity of e-module was valued by three material experts an three media experts by using evaluation sheets and examining with Gregory cross tabulation. Data obtained through limited field tests, wide field tests 1 and wide field tests 2 to improve the results of the e-module product through suggestions and input on the prepared pond. The result of evaluation showed can be concluded that senior high school mathematics e-module based on STEM orienting to HOTS which was developed filled the aspects of validity, practicality, and effectiveness. It could be used in the learning process. The implications of the HOTS-based on STEM-orienting to high school mathematics E-module is very helpful for students to learn at anywhere and anytime independently.